Pengelolaan Karakter Kedisiplinan Di SD Al-Islam 3 Gebang Surakarta - SUMANTO, SUMANTO (2016)
The purpose of this research are: 1) To describe the concept of Discipline management (management) characters in SD Al Islam 3 Gebang Surakarta current 2) Efforts to improve student learning in elementary school Discipline Al Islam 3 Gebang Surakarta. 3) The factors supporting and inhibiting factors Characters Discipline students in elementary Al Islam 3 Gebang Surakarta. This study is a qualitative research approach EMIC and ethics. Data collection techniques used in this study included interviews, observations (observation) and documentation. The results of the study the general implementation of the discipline code running in an orderly and organized, can be seen from the enthusiasm and activeness of students in practice. Although there are some students who are not so concerned with discipline. Efforts to improve Discipline Students in elementary Al Islam 3 Gebang Surakarta. Implementation of business management as a discipline code internalization of Islamic teachings in SD Al-Islam Surakarta 3 cultivation of religious values include: apple morning prayer discipline discipline, and discipline tadarus Qur'an. While the cultivation of moral values including disciplinary matters and Salim, playback murotal and the Divine Name, discipline and discipline clean Friday infaq / alms. Islamic values that can be internalized to the student with the existing character of the value discipline of worship and moral values. Factors supporting and inhibiting factors in improving student learning in elementary school Discipline Al Islam 3 Gebang Surakarta Factors supporting characters discipline education students are) Values of honesty, b) The value of responsibility and c) assessment model on any subject using cognitive assessment (knowledge ), affective (attitude), also psychomotor (skills). Inhibiting factor is the environment that is not good. Keywords: Discipline, Character Education, Elementary School